Optimalisasi Pemilihan Karyawan Penerima Voucher Umroh Menggunakan Metode Analytical Hierarchy Process (AHP) - Ariandi, Sheva Rizky; Suprapto, S; Andika, Sophian; Hadikristanto, Wahyu (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The Analytical Hierarchy Process (AHP) method is applied in selecting the best employees who will receive Umrah vouchers at PT. Tempo Scan Pacific Tbk Indonesia to expedite the selection process. In this research, the AHP method was used to determine four criteria for selecting the best employees, namely Attendance, Target Achievement, Work Initiative, and Teamwork. The sample of employees tested consisted of four people with the importance weight of Attendance 2 times more important than Initiative, Teamwork 3 times more important than Job Targets and Initiative 2 times more important than Job Targets. Attendance Consistency Ratio Value 7.88%, Achievement Target 8.55%, Initiative 9.95% and Teamwork 6.03%. The test results of 4 employees A, B, C and D show that Employee D has the highest value of 0.3614, followed by Employee C with a value of 0.2733, Employee A with a value of 0.2384, and Employee B with a value of 0.1267. Based on these results, it can be concluded that Employee D is the most entitled to receive an Umrah voucher.